A bacterial secreted translocator hijacks riboregulators to control type III secretion in response to host cell contact - Kusmierek, Maria (PLoS Pathog, 2019)
Numerous Gram-negative pathogens use a Type III Secretion System (T3SS) to promote virulence by injecting effector proteins into targeted host cells, which subvert host cell processes. Expression of T3SS and the effectors is triggered upon host cell contact, but the underlying mechanism is poorly understood. Here, we report a novel strategy of Yersinia pseudotuberculosis in which this pathogen uses a secreted T3SS translocator protein (YopD) to control global RNA regulators. Secretion of the YopD translocator upon host cell contact increases the ratio of post-transcriptional regulator CsrA to its antagonistic small RNAs CsrB and CsrC and reduces the degradosome components PNPase and RNase E levels. This substantially elevates the amount of the common transcriptional activator (LcrF) of T3SS/Yop effector genes and triggers the synthesis of associated virulence-relevant traits. The observed hijacking of global riboregulators allows the pathogen to coordinate virulence factor expression and also readjusts its physiological response upon host cell contact.